Effectiveness of Acceptance and Commitment Therapy self-help for carers of people with multiple sclerosis: a feasibility randomised controlled trial - Martin, Kristy-Jane (2018)
Objective: Acceptance and Commitment Therapy (ACT) may be a feasible, accessible and effective intervention to ‘informal’ carers of people with Multiple Sclerosis (MS) who may be experiencing strain as a result of their caring duties. The aim of this study was to assess the feasibility of randomised controlled trial (RCT) of ACT self-help, telephone-supported ACT self-help, compared to usual care (UC). Study objectives related to feasibility and acceptability of the study design and the two chosen interventions and assessing potential effectiveness at both individual and group level.